Assessment of the Readiness for Enterprise Resource Planning (ERP) implementation in Indramayu reviewed through strategy, technology, environment, people, and organization - Setyawan, Ari Dwi (Green Publisher Indonesia, 2025)
This study aims to evaluate the readiness of the Indramayu Regency Government in adopting Enterprise Resource Planning (ERP) as part of the implementation of e-Government. The background of this research is the importance of e-Government to improve the efficiency and transparency of public services, where ERP can play a key role in integrating various government functions. However, the readiness of local governments to adopt ERP is still a major challenge. The method used is Structural Equation Modelling-Partial Least Square (SEM-PLS) combined with the STOPE (Strategy, Technology, Organization, People, & Environment) framework. This approach allows for an in-depth analysis of the causal relationships between variables that affect ERP readiness in e-Government adoption. Data was collected and analyzed to test the influence of five key variables on ERP readiness. The results showed that organizational and human resource variables had a significant influence on ERP readiness, with path coefficient values of 0.490 and 0.240, respectively. On the other hand, the strategy and technology variables did not show significant influence, with path coefficient values of 0.171 and -0.116, respectively. The environmental variable was also insignificant with a path coefficient value of 0.029. In conclusion, ERP readiness in Indramayu Regency is more influenced by internal factors such as management support and human resource readiness, while technology and the environment make a limited contribution. Therefore, improving ERP readiness requires focusing on strengthening internal organizational factors and developing human resource capacity